Gestión de riesgos informáticos a los que se exponen los equipos y programas del departamento informático de la Utmach. - Maxi Cabrera, Mayra Ivonne (My University, 2020)
The age of knowledge is solved through computer systems, virtual services and office potential, capable of improving in every way the daily, work, professional activities and subtly integrate them into society. Although these benefits have revolutionized education, medicine, science and engineering, they carry risks or adverse conditions that are eclipsed by their advantages. As a social responsibility of the accounting and auditing career, the management of computer risks in the IT department of the Technical University of Machala is analyzed, applying an explanatory methodology of analytical character to settle criteria when sequencing a procedure appropriate to the vulnerabilities detected in the study. The results give a qualitative assessment of the risks, analyzing their effects on the different dependencies of the institutional system; However, the biggest problem is the time that degrades all technological benefits without the human resources taking the appropriate measures.
La era del conocimiento se solventa mediante sistemas informáticos, servicios virtuales y potencialidades ofimáticas, capaces de mejorar en todo sentido las actividades diarias, laborales, profesionales e integrarlas sutilmente a la sociedad. Aunque dichas bondades han revolucionado la educación, medicina, ciencias e ingeniería conllevan riesgos o condiciones adversas que son eclipsadas por sus ventajas. Como responsabilidad social de la carrera de contabilidad y auditoría se analiza la gestión de riesgos informáticos en el departamento de informática de la Universidad Técnica de Machala, aplicando una metodología explicativa de carácter analítica para dirimir criterios al secuenciar un procedimiento adecuado a las vulnerabilidades detectadas en el estudio. En los resultados se da una valoración cualitativa de los riesgos, analizando sus afectaciones en las distintas dependencias del sistema institucional; sin embargo, el mayor problema es el tiempo que degrada todas las prestaciones tecnológicas sin que el recurso humano tome las medidas pertinentes.
Keywords: GESTIÓN; RIESGO INFORMÁTICO; HARDWARE; SOFTWARE; SISTEMAS